2013
DOI: 10.1155/2013/329596
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stem Cell as a Potential Treatment for Diabetes

Abstract: Diabetes mellitus (DM) is a group of metabolic diseases in which a person has high blood glucose levels resulting from defects in insulin secretion and insulin action. The chronic hyperglycemia damages the eyes, kidneys, nerves, heart, and blood vessels. Curative therapies mainly include diet, insulin, and oral hypoglycemic agents. However, these therapies fail to maintain blood glucose levels in the normal range all the time. Although pancreas or islet-cell transplantation achieves better glucose control, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…On the other hand, the infusion of BMSCs suppressed helper T-cell development, thus attenuating immune responses and inflammatory damage [147]. Type I and type II diabetes have been the targets of BMSCs therapy [148][149][150][151]. There are several completed and in processing clinical trials registered in the database of U.S National Library of Medicine that used BMSCs in phase I to phase III clinical trials.…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…On the other hand, the infusion of BMSCs suppressed helper T-cell development, thus attenuating immune responses and inflammatory damage [147]. Type I and type II diabetes have been the targets of BMSCs therapy [148][149][150][151]. There are several completed and in processing clinical trials registered in the database of U.S National Library of Medicine that used BMSCs in phase I to phase III clinical trials.…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…The treatment of diabetes mellitus includes diet (Li Volti et al, 2011 ; Marrazzo et al, 2014 ), therapy with insulin and/or oral hypoglycemic agents and pancreas transplantation or pancreatic islets (Logdberg et al, 2003 ). However, because of the limited availability of donor organs, recent studies have focused on the possibility of using stem cells for the treatment of DM (Li and Ikehara, 2013 ).…”
Section: Diabetes and Related Complicationsmentioning
confidence: 99%
“…Extensive stellate cell-mediated fibrosis is a main characteristic of CP as well as pancreatic cancer ( 53 , 54 ). It was observed that bone marrow-derived stem cells could incorporate into the pancreas and differentiate to the exocrine compartment ( 55 ). This differentiation adopted various phenotypes depending on whether cells are recruited to an inflammatory or a carcinogenic pancreas.…”
Section: Chronic Pancreatitis (Cp) and Pancreatic Fibrosismentioning
confidence: 99%